Assessing metarepresentational abilities in adolescence: an exploratory study on relationships between definitional competence and theory of mind - Cornaggia, Alessia; Bianco, Federica; Castelli, Ilaria; Belacchi, Carmen (Frontiers in Psychology, 2024)
Several developmental changes occur in the adolescence, particularly in the metarepresentational domain, which allow and promote an adaptive sociality. We explored the possible relationships between Theory of Mind (ToM) and definitional competences, both metarepresentational, beyond age and gender effects. To reach our goals, we involved 75 adolescents (age range 14 -19 years, M = 15.7, SD = 1.36). ToM was measured through "The Reading the Mind in the Eyes Test" (RMET) and definitional competence was assessed via a new instrument, namely the "Co.De. Scale". Attention was paid to check if results were different when considering mental states vs. non mental states of the scale and emotional words vs. non emotional words. T-tests showed that older adolescents (third-grade of high school) performed better than younger ones (first-grade of high school) in both tasks. Only in male group there were no school grade differences in ToM task. Regression analyses showed that RMET performance predicted the score of Non emotional mental states definitions and, even if marginally, of ToM Words definitions. However, RMET was not a predictor of the general performance in the definitional task, nor on Emotion definitions. Connections with the global adolescents' development and possible educative implications are discussed.